DNA methylation accelerated age as captured by epigenetic clocks influences breast cancer risk - Valencia, Celina I.; Saunders, Devin; Daw, Jennifer; Vasquez, Adria (Frontiers in Oncology, 2023)
Introduction: Breast cancer is the leading form of cancer among women in the United States. Additionally, disparities across the breast cancer continuum continue to increase for minoritized women. The mechanism driving these trends are unclear, however, accelerated biological age may provide key insights for understanding these disease patterns. Accelerated age measured by DNA methylation using epigenetic clocks is to date the most robust method for estimating accelerated age. We synthesize the existing evidence on epigenetic clocks measurement of DNA methylation based accelerated age and breast cancer outcomes. Methods: Our database searches were conducted from February 2022 to April 2022 and yielded a total of 2,908 articles for consideration. We implemented methods using guidance from the PROSPERO Scoping Review Protocol to assess articles on epigenetic clocks and breast cancer outcomes. Results: Five articles were included in this review. Ten epigenetic clocks were used across the five articles demonstrating statistically significant results for breast cancer outcomes. DNA methylation accelerated age varied by sample type. The studies did not consider social factors or epidemiological risk factors. The studies lacked representation of diverse populations. Discussion: Epigenetic clocks measures of DNA methylation age had associative relationship with breast cancer outcomes, however, important social factors that contribute to patterns of methylation were not comprehensively considered in the available literature. More research is needed on DNA methylation age across the lifespan including and in diverse populations. This review demonstrates DNA methylation accelerated age provides key insights for tackling the breast cancer burden and disease disparities of minoritized.